Synergistic antibacterial effects of carbon dots derived from Lactobacillus acidophilus alone and in combination against carbapenem-resistant Klebsiella pneumoniae - Leila Shamkhali; Ashraf Mohabati Mobarez; Seyed Davar Siadat; Hamid Pajavand (Journal of Infection and Public Health)
Background: Non-antibiotic treatments, such as carbon dots (C-dots), are gaining popularity in the search for effective alternatives. We aimed to evaluate the antibacterial properties of C-dots derived from Lactobacillus acidophilus (L-C-dots) alone and in combination against carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates. Methods: Seventy clinical isolates of Klebsiella pneumoniae were tested for carbapenem resistance using a modified carbapenem inactivation assay. To determine the presence of fimH and mrkD genes, which are associated with biofilm formation, polymerase chain reaction (PCR) was conducted. L-C-dots were synthesized using a hydrothermal method and characterized. Furthermore, their antibacterial and anti-biofilm activities were evaluated against CRKP isolates. The combination of L-C-dots with the meropenem antibiotics were also tested using a checkerboard assay. Finally, the influence of L-C-dots on the expression levels of fimH and mrkD genes was examined using quantitative PCR (qPCR). Results: L-C-dots demonstrated significant antibacterial activity against CRKP isolates, with a minimum inhibitory concentration (MIC) of 50 mg/mL and a sub-MIC of 25 mg/mL. L-C-dots effectively inhibited biofilm formation at MIC and sub-MIC concentrations (P ˂ 0.05). Additionally, the L-C-dots had synergistic and additive interactions with the meropenem antibiotics against CRKP isolates, reducing the MIC of both agents. Furthermore, the L-C-dots decreased the expression of the fimH (p< 0.029) and mrkD (p < 0.015) genes. Conclusions: The findings indicate that L-C-dots may serve as a promising new treatment option for CRKP infections. They show potential as a strong therapeutic choice, especially when used in combination with traditional antibiotics.